Identification of Sexual Disinhibition in Dementia by Family Caregivers. (April 2019) - Chapman, Kimberly R.; Tremont, Geoffrey; Malloy, Paul; Spitznagel, Mary Beth
Abstract : Purpose: Sexual disinhibition in dementia is understudied and discrepant frequency rates are reported. Measures designed to capture general disinhibition may under-identify sexual disinhibition, and lack of assessment uniformity may contribute to inconsistent endorsement. The current study aimed to determine: (1) whether an item from a commonly used measure tapping into general disinhibition would detect sexual disinhibition, (2) whether differently worded items specifically addressing sexual disinhibition would elicit inconsistent endorsement, and (3) whether different caregiver types would yield discrepant endorsement. Methods: Data for this cross-sectional, observational study were collected online using items from the Neuropsychiatric Inventory, Cohen-Mansfield Agitation Inventory, and novel items developed to assess sexual disinhibition. Patients: In total, 779 family dementia caregivers were recruited from social media caregiver groups. Results: In total, 26.2% of caregivers who explicitly endorsed sexual disinhibition did not endorse general disinhibition. Frequency of endorsement for sexual disinhibition differed depending upon item wording and nature of the caregiver relationship, including higher endorsement by spouses overall. Discussion: Inquiring generally about disinhibition may under-identify presence of sexual disinhibition. Lack of standardization may contribute to inconsistent frequency rates and characterization of this problem. More work is needed to better understand and identify sexual disinhibition in dementia.